Factors influencing flexibility among UiTM's Silat practitioners / Zul Hafizi Zulkiflee - Zulkiflee, Zul Hafizi (Faculty of Education, 2014)
In Malaysia, the first of martial art is known as Silat. There are 200 types of silat in this country such as Silat Seni Gayong Malaysia, Silat Harimau, Silat Cekak and etc. A study was conducted in order to investigate the level of flexibility among Silat Practitioner in diverse level of belt. This research is to examine the different of belt level of silat practitioner affect flexibility and if the skills in different level of belt affect flexibility of belt affect flexibility of silat practitioner. Furthermore, this studies also to investigate the factor that influences the flexibility among Silat practitioner in different level of belt. The study utilized qualitative method and experimental approach. The respondents are picked randomly from Silat Practitioner in UiTM, Shah Alam. Therefore, qualitative research is useful to collect data from the respondent which is Silat Practitioner. The numbers of sample involved in this study were 20 persons of Silat Practitioner. The findings obtained from this study and review the findings to address the research questions. There are two sections; the first section provides the discussion and summary of the research followed by the second section which discusses the implication for the study